Implementasi Pembelajaran Al-Qur'an Metode Ummi untuk Meningkatkan Kemampuan Bacaan Tartil Siswa: Studi Kasus di SDII Luqman Al-Hakim 01 Batam - Nurul Fadhilah; Nabia Nabia; Deva Julita; Noviani Rabiatul Adawiyah; Enik Nurfaizah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The quality of Al-Qur'an recitation is often hindered by non-ideal teacher-student ratios and low student focus. This study aims to describe the implementation of the Ummi method to improve students' tartil skills at SDII Luqman Al Hakim 01 Batam through the School-Based Internship (PLP) program. The research follows a qualitative descriptive method with a case study approach. Data were gathered through participant observation and documentation, then analyzed through data reduction, display, and conclusion drawing. The results indicate that the presence of internship students helps maintain a proportional teacher-student ratio (1:11), allowing for more intensive guidance. The systematic application of the seven stages of the Ummi method shows improvements in makhraj accuracy and student fluency. Furthermore, modifications to the seating arrangement proved effective in minimizing focus distractions, which directly correlates with the progress recorded in students' achievement books. This study concludes that standardized methodology, systemic school support, and adaptive classroom management are essential factors in optimizing students' tartil recitation skills.